Precision measurement of the ratio of the [lambda] 0b to B [Oberstrich] 0 lifetimes - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; et al. (Physics letters, 2014)
The LHCb measurement of the lifetime ratio of the Λb0 baryon to the B¯0 meson is updated using data corresponding to an integrated luminosity of 3.0 fb−1 collected using 7 and 8 TeV centre-of-mass energy pp collisions at the LHC. The decay modes used are Λb0→J/ψpK− and B¯0→J/ψπ+K−, where the π+K− mass is consistent with that of the K¯⁎0(892) meson. The lifetime ratio is determined with unprecedented precision to be 0.974±0.006±0.004, where the first uncertainty is statistical and the second systematic. This result is in agreement with original theoretical predictions based on the heavy quark expansion. Using the current world average of the B¯0 lifetime, the Λb0 lifetime is found to be 1.479±0.009±0.010 ps.